PENGARUH PENERAPAN LKPD BERBASIS DISCOVERY LEARNING BERBANTUAN MIND MAP TERHADAP KOMPETENSI IPA PESERTA DIDIK KELAS VII SMPN 6 BUKITTINGGI - Ernita Susanti; Ratnawulan Ratnawulan; Zulhendri Kamus (Universitas Negeri Padang, 2015)
One factor that makes Students having low competency in Natural Science is the use of ineligible worksheet which don’t matching with teacher’s learning method applied. One of solutions to overcome the issue is the use of student worksheet based on Discovery Learning assisted by Mind Map. Kind of research is quasi experimental research by design of Randomized Control Group Only Design. The population of this research is students of SMPN 6 Bukittinggi grade 7th in 2014/2015. Sample is taken based on Purposive Sampling technique. Research cover competency of attitude, cognitive, and skill aspect. The research instrument is observation form for attitude and skill aspect than test for cognitive aspect. The data was analysed by using t- test. Based on analysis of data, average of experimental sample competency more than control sample. The result of the research shows that the using of student worksheet based on Discovery Learning assisted by Mind Map gives significant impact to students’ Natural Science competency of SMP Negeri 6 Bukittinggi grade 7th at 0,05 significance level